Classication of Agricultural Fields in Satellite Images Using Two-Dimensional Hidden Markov Models - Baumgartner, J.; Giménez, J.; Pucheta, J.; Flesia, A. G. (2021)
Fil: Baumgartner, J. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.